The Effect of Accountability and Transparency on Interest in Paying Zakat at the National Amil Zakat Agency of Buton Regency With Religiosity as a Moderation - Amalia, Lestari Rezki Nurul; Haliah, Haliah; Nirwana, Nirwana (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2024)
Introduction: The Buton Regency National Zakat Amil Agency has the potential to pay zakat by increasing accountability, transparency, and religiosity which can be a factor in advancing the level of community welfare. Objectives: This research aims to determine the effect of accountability and transparency on interest in paying zakat and the relationship between religiosity as moderation in strengthening the influence of accountability and transparency on interest in paying zakat. Method: This research was conducted quantitatively and used a questionnaire as a data collection method. The subjects of this research were 150 muzakki BAZNAS (National Amil Zakat Agency) located in Buton Regency. The data analysis method uses Structural Equation Models with Partial Least Square (PLS). Results: The research results show that accountability and transparency regarding interest in paying zakat have positive and significant results. This research also proves that accountability and transparency on interest in paying zakat are significant with religiosity as a moderating variable that strengthens the influence of accountability and transparency on interest in paying zakat. Implications: These results contribute to the development of a model in research that accounting and transparency in zakat institutions with religiosity as moderation can influence interest in paying zakat.